ANALISIS ISU-ISU PENDIDIKAN DI SEKOLAH DASAR: KEAHLIAN GURU DAN PERKEMBANGAN PSIKOLOGI PESERTA DIDIK DALAM MENGHADAPI TANTANGAN PEMBELAJARAN ABAD 21 - Selvia Elpitri; Salsabila Maghfirah Ramadhani; Harisa Dzikra Adity; Elfina Nazhifah Salwa; Haifa Sakinah; Padil Asrodi; Reinita (STKIP Subang, 2026)
This study aims to analyze educational issues at SD Negeri 19 Alai Sako related to teachers’ expertise and students’ psychological development in addressing 21st-century learning challenges. The study employed a descriptive qualitative method, with data collected through in-depth interviews with fifth-grade teachers as the primary informants. The findings revealed that issues regarding teacher competence include limited integration of technology in learning, weak mastery of subject matter, ineffective communication skills, a reliance on monotonous lecture-based methods, and difficulties managing emotions and professional stress. Meanwhile, issues regarding students’ psychological development include bullying behavior, daily misbehavior, lack of learning awareness, low learning motivation, laziness in learning, and low self-confidence. These two dimensions of problems are interrelated and impact both the quality of the learning process and its outcomes. Mitigation efforts include continuous professional development training for teachers, strengthening teachers’ self-reflection, collaboration between teachers and parents, the use of digital media, the implementation of responsive assessment, and enhancing teachers’ understanding of students’ developmental psychology. The integration of teachers’ competencies and psychological approaches is a key solution in realizing effective, meaningful, and student-centered learning